Microtubule Severing Protein Fignl2 Contributes to Endothelial and Neuronal Branching in Zebrafish Development - Dong, Zhangji; Chen, Xu; Li, Yuanyuan; Zhuo, Run; Lai, Xiaona; Liu, Mei (Frontiers in Cell and Developmental Biology, 2021)
Previously, fidgetin (fign) and its family members fidgetin-like 1 (fignl1) and fidgetin-like 2 (fignl2) were found to be highly expressed during zebrafish brain development, suggesting their functions in the nervous system. In this study, we report the effects of loss-of-function of these genes on development. We designed and identified single-guide RNAs targeted to generate fign, fignl1, and fignl2 mutants and then observed the overall morphological and behavioral changes. Our findings showed that while fign and fignl1 null mutants displayed no significant defects, fignl2 null zebrafish mutants displayed pericardial edema, reduced heart rate, and smaller eyes; fignl2 null mutants responded to the light-darkness shift with a lower swimming velocity. fignl2 mRNAs were identified in vascular endothelial cells by in situ hybridization and re-analysis of an online dataset of single-cell RNAseq results. Finally, we used morpholino oligonucleotides to confirm that fignl2 knockdown resulted in severe heart edema, which was caused by abnormal vascular branching. The zebrafish fignl2 morphants also showed longer axonal length and more branches of caudal primary neurons. Taken together, we summarize that Fignl2 functions on cellular branches in endothelial cells and neurons. This study reported for the first time that the microtubule-severing protein Fignl2 contributes to cell branching during development.